Optical Emission Spectroscopic Technique for Diagnosis of Plasma Parameters of the Comet Tail - Yaseen, Waleed Ibrahim; Al-Juboori, Omar; Hadi, Khalid A. (Iraqi Journal of Science, 2025)
In this work, the optical emission spectroscopy technique was employed to diagnose the plasma and solar wind parameters of Comet C/2020 F3 from July 21 to July 31, 2020. Datasets of comet C2020 F3 (NEOWISE) were gathered using the Cassegrain telescope camera CTK-II providing information within the visible spectrum, particularly emission lines within the wavelength range of 560 to 636 nanometers. The investigation utilized a two-line ratio method to scrutinize the spectrum of the comet over a five-day period from July 21 to July 31, 2020. Furthermore, various plasma parameters such as electron temperature, electron density, Debye length, and plasma frequency were determined. The study also delved into solar wind parameters that align with the comet plasma parameters, including solar wind temperature (in Kelvin), proton density (measured in 1/cm³), solar wind speed (in kilometers per second), and magnetic field strength (denoted as Bx, By, and Bz) in nT. The findings obtained from the analysis of the spectrum were employed to identify the chemical composition of the comet plasma. The results of this study are evident in a correlation between the intensity of these emissions and the distance of the comet from the Sun. It was observed that the heightened values of solar wind speed and temperature, particularly between the 25th and 28th of July, influenced the temperature and electron density of the plasma. During the 30th and 31st days of July, there was a decrease in both electron temperature and electron density as the comet moved farther away from the Sun.